Understanding And Responding To The Victimisation Of Lgbtqia+ Population - Tiwari, Divya; Uzma, Uzma (Journal of Neonatal Surgery, 2025)
Imagine the social stature of homosexuals, being caged in a body without any specific sexual or gender identity in a society that is discriminatory and not gender-just. Questions of violence, vulnerability of sexual and gender minorities remain occupy a focal place globally and in Indian public discourse as well. In recent years, attitude towards Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual and other with marginalized identities have shifted slightly in India with an element of third gender in its social structure. However, violence against LGBTQIA+ population still prevails in India. Further despite the notion that our society is becoming more welcoming victimization differences appear to have stabilized. More research using probabilistic sampling methods, standardized metrics and bigger sample of LGBTQIA+ population are needed. Due to existing victimization and prejudice, this identical population is being subjected to discriminations and deprived of various Constitutional rights. Yet study finds a policy implementation gap in this area. Gender equality is a core principle of the Sustainable Development Goals (SDGs), with SDG 5 specifically focusing on achieving gender equality and empowering all women and girls and gender queers but it’s also crucial for achieving all other SDGs. This paper aims to understand how legal ideas, social phenomenon and ground level practices and institutions function within the cultural, economic, political and social context of LGBTQIA+ population.